Integral nonlocal approach to model interface decohesion in FFT solvers. (15th February 2021) - Sharma, L.; Peerlings, R.H.J.; Geers, M.G.D.; Roters, F.
Abstract: In this work, the capability of Fast Fourier transform (FFT) solvers is extended to interface damage modelling. The grid based discretization necessitates to incorporate the cohesive fracture concept using the ideas of continuum damage mechanics and by approximating the sharp interfaces as interphases. The interface crack opening and sliding is modelled using anisotropic kinematics. The decohesion model and the related nonlocal regularization within the interphases, including triple junctions, are discussed in the context of regular grid discretization. An integral nonlocal approach is used to obtain delocalized deformation and it also enables the intended scaling of cohesive parameters. The response of the model—in terms of overall response and the insensitivity of dissipation to interphase thickness—is discussed in a one-dimensional study. Crack propagation modelling along straight and non-straight interface paths in two dimensional polycrystals is also presented. Highlights: Integral averaging approach to model interfaces as nonlocal interphases is presented. Theoretical scaling of parameters is facilitated by anisotropic regularization. Demonstration of the model on polycrystals is presented.